ChemInform Abstract: Copper‐Catalyzed Aerobic Cascade Cycloamination and Acyloxylation: A Direct Approach to 4‐Acyloxy‐1H‐pyrazoles. Issue 33 (August 2015) - Ding, Zhengwei; Tan, Qitao; Gao, Mingchun; Xu, Bin
Abstract A novel protocol for the regioselective synthesis of multisubstituted 4‐acyloxy‐pyrazoles such as (III) and (V) in a single step from hydrazones and carboxylic acids is reported.